(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Transfer pricing remains a contentious issue in global taxation, often between legal tax planning and unethical tax avoidance. This study aims to examine the role of transfer pricing in facilitating tax avoidance, particularly in developing countries such as Indonesia. Utilizing a Systematic Literature Review (SLR) approach based on the PRISMA framework, 24 peer-reviewed articles from reputable databases were analyzed. The review finds that a majority of the studies indicate a positive association between transfer pricing practices and corporate tax avoidance. From the lens of agency theory, transfer pricing strategies may serve the interests of corporate principals by reducing tax burdens; however, they can also create ethical concerns and fiscal imbalances, especially when used to shift profits to low-tax jurisdictions. In response, this study emphasizes the urgent need for stronger regulatory frameworks, greater transparency, and international cooperation to ensure that transfer pricing practices uphold fairness and do not undermine national tax systems.